show that the points A(0,0), B(3,0), C(4,1) , and D (1,1) form a parallelogram
Answers
just see the attachment !
hope if helps !
follow me !
![](https://hi-static.z-dn.net/files/d53/5a7525097f6653ae5e6ea30c4d0528d4.jpg)
![](https://hi-static.z-dn.net/files/db6/566bdca5b15a665d6c2a30b502923ab4.jpg)
Answer:
Answer:AB= CD, AC=BD.
Answer:AB= CD, AC=BD.Step-by-step explanation:
Answer:AB= CD, AC=BD.Step-by-step explanation:AB^2 = (3)^2 + (0) ^2
Answer:AB= CD, AC=BD.Step-by-step explanation:AB^2 = (3)^2 + (0) ^2 AB^2 =9
Answer:AB= CD, AC=BD.Step-by-step explanation:AB^2 = (3)^2 + (0) ^2 AB^2 =9 AB = 3
Answer:AB= CD, AC=BD.Step-by-step explanation:AB^2 = (3)^2 + (0) ^2 AB^2 =9 AB = 3
Answer:AB= CD, AC=BD.Step-by-step explanation:AB^2 = (3)^2 + (0) ^2 AB^2 =9 AB = 3 BC^2= (3-4)^2 + (1)^2
Answer:AB= CD, AC=BD.Step-by-step explanation:AB^2 = (3)^2 + (0) ^2 AB^2 =9 AB = 3 BC^2= (3-4)^2 + (1)^2 BC^2=1+1
Answer:AB= CD, AC=BD.Step-by-step explanation:AB^2 = (3)^2 + (0) ^2 AB^2 =9 AB = 3 BC^2= (3-4)^2 + (1)^2 BC^2=1+1BC= √2
Answer:AB= CD, AC=BD.Step-by-step explanation:AB^2 = (3)^2 + (0) ^2 AB^2 =9 AB = 3 BC^2= (3-4)^2 + (1)^2 BC^2=1+1BC= √2CD^2 = (4-1)^2 + (1-1)^2
Answer:AB= CD, AC=BD.Step-by-step explanation:AB^2 = (3)^2 + (0) ^2 AB^2 =9 AB = 3 BC^2= (3-4)^2 + (1)^2 BC^2=1+1BC= √2CD^2 = (4-1)^2 + (1-1)^2CD^2= 9+0
Answer:AB= CD, AC=BD.Step-by-step explanation:AB^2 = (3)^2 + (0) ^2 AB^2 =9 AB = 3 BC^2= (3-4)^2 + (1)^2 BC^2=1+1BC= √2CD^2 = (4-1)^2 + (1-1)^2CD^2= 9+0CD = 3
Answer:AB= CD, AC=BD.Step-by-step explanation:AB^2 = (3)^2 + (0) ^2 AB^2 =9 AB = 3 BC^2= (3-4)^2 + (1)^2 BC^2=1+1BC= √2CD^2 = (4-1)^2 + (1-1)^2CD^2= 9+0CD = 3AD^2= (1)^2 +(1)^2
Answer:AB= CD, AC=BD.Step-by-step explanation:AB^2 = (3)^2 + (0) ^2 AB^2 =9 AB = 3 BC^2= (3-4)^2 + (1)^2 BC^2=1+1BC= √2CD^2 = (4-1)^2 + (1-1)^2CD^2= 9+0CD = 3AD^2= (1)^2 +(1)^2AD^2= 2
Answer:AB= CD, AC=BD.Step-by-step explanation:AB^2 = (3)^2 + (0) ^2 AB^2 =9 AB = 3 BC^2= (3-4)^2 + (1)^2 BC^2=1+1BC= √2CD^2 = (4-1)^2 + (1-1)^2CD^2= 9+0CD = 3AD^2= (1)^2 +(1)^2AD^2= 2AD = √2
Answer:AB= CD, AC=BD.Step-by-step explanation:AB^2 = (3)^2 + (0) ^2 AB^2 =9 AB = 3 BC^2= (3-4)^2 + (1)^2 BC^2=1+1BC= √2CD^2 = (4-1)^2 + (1-1)^2CD^2= 9+0CD = 3AD^2= (1)^2 +(1)^2AD^2= 2AD = √2 AC^2 = (4)^2+(1)^2
Answer:AB= CD, AC=BD.Step-by-step explanation:AB^2 = (3)^2 + (0) ^2 AB^2 =9 AB = 3 BC^2= (3-4)^2 + (1)^2 BC^2=1+1BC= √2CD^2 = (4-1)^2 + (1-1)^2CD^2= 9+0CD = 3AD^2= (1)^2 +(1)^2AD^2= 2AD = √2 AC^2 = (4)^2+(1)^2AC^2= 16+1
Answer:AB= CD, AC=BD.Step-by-step explanation:AB^2 = (3)^2 + (0) ^2 AB^2 =9 AB = 3 BC^2= (3-4)^2 + (1)^2 BC^2=1+1BC= √2CD^2 = (4-1)^2 + (1-1)^2CD^2= 9+0CD = 3AD^2= (1)^2 +(1)^2AD^2= 2AD = √2 AC^2 = (4)^2+(1)^2AC^2= 16+1AC= √17
Answer:AB= CD, AC=BD.Step-by-step explanation:AB^2 = (3)^2 + (0) ^2 AB^2 =9 AB = 3 BC^2= (3-4)^2 + (1)^2 BC^2=1+1BC= √2CD^2 = (4-1)^2 + (1-1)^2CD^2= 9+0CD = 3AD^2= (1)^2 +(1)^2AD^2= 2AD = √2 AC^2 = (4)^2+(1)^2AC^2= 16+1AC= √17BD^2= (3-1)^2+(1)^2
Answer:AB= CD, AC=BD.Step-by-step explanation:AB^2 = (3)^2 + (0) ^2 AB^2 =9 AB = 3 BC^2= (3-4)^2 + (1)^2 BC^2=1+1BC= √2CD^2 = (4-1)^2 + (1-1)^2CD^2= 9+0CD = 3AD^2= (1)^2 +(1)^2AD^2= 2AD = √2 AC^2 = (4)^2+(1)^2AC^2= 16+1AC= √17BD^2= (3-1)^2+(1)^2BD^2= 4+1
Answer:AB= CD, AC=BD.Step-by-step explanation:AB^2 = (3)^2 + (0) ^2 AB^2 =9 AB = 3 BC^2= (3-4)^2 + (1)^2 BC^2=1+1BC= √2CD^2 = (4-1)^2 + (1-1)^2CD^2= 9+0CD = 3AD^2= (1)^2 +(1)^2AD^2= 2AD = √2 AC^2 = (4)^2+(1)^2AC^2= 16+1AC= √17BD^2= (3-1)^2+(1)^2BD^2= 4+1BD = √5
Answer:AB= CD, AC=BD.Step-by-step explanation:AB^2 = (3)^2 + (0) ^2 AB^2 =9 AB = 3 BC^2= (3-4)^2 + (1)^2 BC^2=1+1BC= √2CD^2 = (4-1)^2 + (1-1)^2CD^2= 9+0CD = 3AD^2= (1)^2 +(1)^2AD^2= 2AD = √2 AC^2 = (4)^2+(1)^2AC^2= 16+1AC= √17BD^2= (3-1)^2+(1)^2BD^2= 4+1BD = √5SO THAT,
Answer:AB= CD, AC=BD.Step-by-step explanation:AB^2 = (3)^2 + (0) ^2 AB^2 =9 AB = 3 BC^2= (3-4)^2 + (1)^2 BC^2=1+1BC= √2CD^2 = (4-1)^2 + (1-1)^2CD^2= 9+0CD = 3AD^2= (1)^2 +(1)^2AD^2= 2AD = √2 AC^2 = (4)^2+(1)^2AC^2= 16+1AC= √17BD^2= (3-1)^2+(1)^2BD^2= 4+1BD = √5SO THAT, AB=CD, AC= BD,AD= BC
Answer:AB= CD, AC=BD.Step-by-step explanation:AB^2 = (3)^2 + (0) ^2 AB^2 =9 AB = 3 BC^2= (3-4)^2 + (1)^2 BC^2=1+1BC= √2CD^2 = (4-1)^2 + (1-1)^2CD^2= 9+0CD = 3AD^2= (1)^2 +(1)^2AD^2= 2AD = √2 AC^2 = (4)^2+(1)^2AC^2= 16+1AC= √17BD^2= (3-1)^2+(1)^2BD^2= 4+1BD = √5SO THAT, AB=CD, AC= BD,AD= BCTHIS IS A PARALLOGRAM ..............